Effect of supporting electrolyte for Cu2+ detection using Pencil Lead Electrode modified with Silver Thin Layer - Zulfa, Khairunnisa (UIR Press, 2024)
Cu2+ metal ions are a type of essential heavy metal, which in small amounts are needed by living things, but in large amounts are toxic and thus harmful to organisms and the environment. In this study, an electroanalytical approach was carried out in detecting Cu2+ using a modified Pencil Lead Electrode with a thin layer of silver by cyclic voltammetric method. A thin layer of silver was deposited on the surface of the Pencil Lead Electrode by electrodeposition with a potential scan of -0.5 V to +0.8 V. Effect of supporting electrolytes was studied. The results showed that Ag/PLE gave a better response than PLE with optimum supporting electrolyte of 0.1 M HClO4.